The divorcées - Beaird, Rowan (Flatiron Books, 2024)
"For fans of Beautiful Ruins and Lessons in Chemistry, a novel set at a 1950s Reno "divorce ranch," about the complex friendship between two women who dare to imagine a different future "A delicious literary page-turner from a fierce new voice." -Rebecca Makkai Lois Saunders thought that marrying the right man would finally cure her loneliness. But as picture-perfect as her husband is, she is suffocating in their loveless marriage. In 1951, though, unhappiness is hardly grounds for divorce-except in Reno, Nevada. At the Golden Yarrow, the most respectable of Reno's famous "divorce ranches," Lois finds herself living with half a dozen other would-be divorcees, all in Reno for the six weeks' residency that is the state's only divorce requirement. They spend their days riding horses and their nights flirting with cowboys, and it's as wild and fun as Lake Forest, Illinois, is prim and stifling. But it isn't until Greer Lang arrives that Lois's world truly cracks open. Gorgeous, beguiling, and completely indifferent to societal convention, Greer is unlike anyone Lois has ever met-and she sees something in Lois that no one else ever has. Under her influence, Lois begins to push against the limits that have always restrained her. But how much can she really trust her mysterious new friend? And how far will she go to forge her independence, on her own terms? Set in the glamorous, dizzying world of 1950s Reno, where housewives and movie stars rubbed shoulders at gin-soaked casinos, The Divorcees is a riveting page-turner and a dazzling exploration of female friendship, desire, and freedom"--